Morphometric parameters of dental pulp in immature teeth in a sheep model after mechanical pulp exposure and restoration with reinforced zinc oxide-eugenol - Eshaghali Saberi; Zahra Heidari; Hamidreza Mahmoudzadeh-Sagheb; Mahdieh Narouei; Lida Jafari; Alireza Mahmoudzadeh-Sagheb; Mahmoud Saadatian (Wolters Kluwer Medknow Publications, 2024)
Background: The aim of the study was to investigate the morphometric parameters of dental pulp in open apices immature teeth in a sheep model after mechanical pulp exposure and restoration with reinforced zinc oxide-eugenol. Materials and Methods: In this experimental study, a total of 12 immature mandibular central incisors from six adult male sheep, weighing 30-40 kg and with the age of 1 year old with Merino race were examined. After anesthesia, the pulps of the teeth in the case group were mechanically exposed and then were restored with reinforced zinc oxide-eugenol and amalgam. In the control group, the teeth remained intact. The animals were sacrificed at intervals of 2, 4, 6, and 8 weeks (E2, E4, E6, and E8) in the case and 2 and 8 weeks (C2 and C8) in the control groups. Then, their teeth were removed with the surrounding supporting tissues and alveolar bones. Tissue processing and staining were done, and the sections were examined under a light microscope. The Kruskal-Wallis and Mann-Whitney U tests were used to analyze the data and compare the changes between the two groups. P < 0.05 was considered statistically significant. Results: In response to mechanical exposure, reparative or tertiary dentin was formed, and its thickness increased during the time of the study. The thickness of the odontoblastic layer in the E4 group was the highest amount. The pulp chamber diameter in the C2 group was significantly larger than the other groups, and the diameter of the apical foramen in the E8 was decreased significantly compared to the controls (P < 0.05). Conclusion: In response to mechanical exposure and restoration with reinforced zinc oxide-eugenol, some morphometric parameters of the dental pulp changed significantly in the sheep model compared to the controls.